Liver inflammation and hepatobiliary cancers - Leone, Valentina; Ali, Sheikh Adnan; Weber, Achim; Tschaharganeh, Darjus-Felix; Heikenwalder, Mathias (Trends in cancer, 2021)
Immune regulation has an important role in cancer development, particularly in organs with continuous exposure to environmental pathogens, such as the liver and gastrointestinal tract. Chronic liver inflammation can lead to the development of hepatobiliary cancers, namely hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (iCCA), or combined HCC (cHCC)-CCA. In this review, we discuss the link between oxidative stress and the hepatic immune compartments, as well as how these factors trigger hepatocyte damage, proliferation, and eventually cancer initiation and its sustainment. We further give an overview of new anticancer therapies based on immunomodulation.
Available online 2 March 2021
Gesehen am 19.07.2021